HeT-A, a transposable element specifically involved in "healing" broken chromosome ends in Drosophila melanogaster. - Biessmann, H (1992)
Eight terminally deleted Drosophila melanogaster chromosomes have now been found to be "healed." In each case, the healed chromosome end had acquired sequence from the HeT DNA family, a complex family of repeated sequences found only in telomeric and pericentric heterochromatin. The sequences were apparently added by transposition events involving no sequence homology. We now report that the sequences transposed in healing these chromosomes identify a novel transposable element, HeT-A, which makes up a subset of the HeT DNA family. Addition of HeT-A elements to broken chromosome ends appears to be polar. The proximal junction between each element and the broken chromosome end is an oligo(A) tract beginning 54 nucleotides downstream from a conserved AATAAA sequence on the strand running 5' to 3' from the chromosome end. The distal (telomeric) ends of HeT-A elements are variably truncated; however, we have not yet been able to determine the extreme distal sequence of a complete element. Our analysis covers approximately 2,600 nucleotides of the HeT-A element, beginning with the oligo(A) tract at one end. Sequence homology is strong (greater than 75% between all elements studied). Sequence may be conserved for DNA structure rather than for protein coding; even the most recently transposed HeT-A elements lack significant open reading frames in the region studied. Instead, the elements exhibit conserved short-range sequence repeats and periodic long-range variation in base composition. These conserved features suggest that HeT-A elements, although transposable elements, may have a structural role in telomere organization or maintenance.